La necesidad de aumentar las revistas científicas en la Orinoquia (2008)
Titulo en ingles: The need for increasing scientific journal production in the Orinoquia region of ColombiaRESUMEN: Con el lema “La ciencia que no se ve no existe”  se realizo recientemente en Toluca (México)   el Primer Taller Internacional de Editores del Sistema de Información Científica Redalyc,   a este evento asistieron 230 editores representando a 103 revistas científicas de 12 diferentes países de Iberoamérica.ABSTRACT: The slogan “Science which you can’t see doesn’t exist” was used recently at the First International Workshop for Scientific Information System Editors organised by the Latin-American and Caribbean, Spanish and Portuguese Scientific Jour- nals’ Network (Red de Revistas Científicas de América Latina y el Caribe, España y Portugal – Redalyc). It was held in Toluca (México) and 230 editors representing 103 scientific journals from 12 different Latin-American countries attended this event.